Present Scenario, Possibilities and Challenges of Women Education in India: The Impact of Women's Education on Health and Empowerment in India (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Education is the process that liberates the mind. It’s liberation from all styles of darkness and ignorance. Women’s literacy is important for economic viability and independence. Acquisition of knowledge is one among the prerequisites of human development. Today all development agencies agree on the importance of teaching women so as to push and maintain family education, health, nutrition and general well-being. The aim of education should be to coach women in such a way that they apply their acquired knowledge to the pursuits of existence and fit them for the position they need to fill. Education for women should be directed towards their holistic development. Education enhances a woman’s sense of her own health needs and perspectives and her power to create any health and birth control decisions. This successively, helps to cut back child and maternal mortality and morbidity rates. The rise within the education of women and women contributes to greater empowerment of women, to a postponement of the age of marriage and to a discount within the size of the families. Women’s literacy is important for economic viability and independence. Acquisition of information is one in all the prerequisites of human development. Today all development agencies agree on the importance of training women so as to push and maintain family education, health, nutrition and general well-being. The aim of education should be to coach women in such the simplest way that they apply their acquired knowledge to the pursuits of everyday life and fit them for the position they need to fill. Education enhances a woman’s sense of her own health needs and perspectives and her power to form any health and birth control decisions. This successively, helps to cut back child and maternal mortality and morbidity rates. The rise within the education of women and women contributes to greater empowerment of women, to a postponement of the age of marriage and to a discount within the size of the families.